1974
DOI: 10.1172/jci107626
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Stimulation of Vasopressin Release during Beta Adrenergic Stimulation with Isoproterenol

Abstract: A B S T R A C T Recent studies have demonstrated that the antidiuresis associated with intravenous (i.v.) infusion of the beta adrenergic agonist, isoproterenol (ISO), is mediated by release of endogenous vasopressin. To examine whether beta-adrenergic stimulation causes vasopressin release by a direct cerebral action, ISO was infused into the carotid artery in a dose estimated to equal the amount of catecholamine reaching the cerebral circulation in the i.v. studies. This intracarotid infusion did not alter r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

1974
1974
2005
2005

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 20 publications
0
14
1
Order By: Relevance
“…In these studies performed in dogs with intact neurohypophyseal tracts but denervated baroreceptors, hypoxia did not significantly alter either Uosm or CH20 Thus, these studies suggest that hypoxia may result in release of AVP through induction of alterations in afferent parasympathetic neural tone. In previous studies in which antidiuretic hormone release appeared to be mediated through alterations in afferent parasympathetic tone, decreases in MAP and(or) CO were present (30,42,46). No such alterations in MAP or CO were observed with hypoxia in the present study.…”
Section: Resultscontrasting
confidence: 54%
See 2 more Smart Citations
“…In these studies performed in dogs with intact neurohypophyseal tracts but denervated baroreceptors, hypoxia did not significantly alter either Uosm or CH20 Thus, these studies suggest that hypoxia may result in release of AVP through induction of alterations in afferent parasympathetic neural tone. In previous studies in which antidiuretic hormone release appeared to be mediated through alterations in afferent parasympathetic tone, decreases in MAP and(or) CO were present (30,42,46). No such alterations in MAP or CO were observed with hypoxia in the present study.…”
Section: Resultscontrasting
confidence: 54%
“…Such hypophysectomized animals have been demonstrated to respond normally to exogenous vasopressin (31). Thus, this model has been used succes-sfully to delineate the role of endogenous vasopressin in the antidiuretic response to a variety of stimuli (24,30,31,(42)(43)(44)(45)(46). In the present study, removal of the source of vasopressin completely abolished the antidiuretic response of hypoxia.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Such hypophysectomized animals may at times have lower mean arterial blood pressures and filtration rates than intact animals, but these animals nevertheless have been adequately shown to respond to exogenous vasopressin (15). This model has therefore proved very useful in delineating the role of endogenous vasopressin in various circumstances in which renal water excretion may be altered, such as during alpha (15) and beta (17) adrenergic stimulation, bilateral cervical vagotomy (16), angiotensin (17), nicotine administration (18), or atrial tachycardia (19), In the present study, acute TIVC constriction was found to have only a slight effect on U..m (87+5 to 104+9 mosmols/kg) in animals in which the source of vasopressin had been removed. Even this modest effect was not significantly reversible.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to nicotine (25), these stimuli include systemic alpha (30) and beta (31) adrenergic stimulation, acute constriction of the thoracic inferior vena cava (32), left atrial distention (33), atrial tachycardia (34), and hypoxia (35). From these results has emerged the hypothesis that the nonosmotic release of vasopressin may have evolved as an integral part of the alarm reaction (36).…”
Section: Plasma Vasopressin In Glucocorticoid Deficiencymentioning
confidence: 99%